THE EFFECT OF SERVICE QUALITY ON CONSUMER PURCHASE INTEREST IN MAS KORI STORE WITH PRICE AS A MEDIATION VARIABLE (JURNAL MANAJEMEN DAN BISNIS, 2022)
This research was conducted at the Mas Kori Store. The purpose of this study was to analyze the effect of service quality on price, service quality on buying interest and price on buying interest and the effect of service quality on consumer buying interest mediated by prices at Mas Kori Stores. Researchers took a sample of 100 people at Mas Kori Store consumers. This sampling method was chosen by random sampling technique at random. The data of this study were analyzed using quantitative methods and all data obtained were processed by path analysis which was operated through the IBM SPSS Version 21 Application and the Sobel Calculator. The results of this study indicate that: (1) Service quality has a positive effect on prices. (2) Service quality has a positive effect on buying interest. (3) Price has a positive effect on buying interest. (4) Price mediates the effect of service quality on buying interest.